پاکستانی معاشرت میں آزاد خیالی(لبرل ازم)کے بڑھتے رجحانات کا تحقیقی مطالعہ (Al-Aasar, 2025)
The basis of the ideology of Pakistan in all respects is Islam and the existence of Pakistan owes its existence to the two-nation ideology. Millions of Muslims sacrificed their lives to achieve this kingdom of God. It is also an undisputed fact that Islam is a complete system of life. It not only guides every aspect of our individual lives but also ignites the collective consciousness. Islam not only commands its followers to perform acts of worship but also creates rules and regulations for socializing. But this is pity that in the past few decades, Hindusim and Western civilization have thickened in the Pakistani society and have started creating doubts in the hearts and minds of the new generations, especially about Islam, Islamic civilization and culture in general, and have expressed a fear that if we do not train the new generation on Islamic script, where will our future generations go? May it not happen that we, as servant of Allah Almight, will be guilty and our deeds will be put to death on this day. As a nation, we are responsible for the moral, social, cultural and economic destruction, where elements hostile to Islam. Pakistan is also trying with all their might to defeat this God-given country at every level.